the Exploitation in James Mcbride’s the Good Lord Bird: Exploitation in James Mcbride’s the Good Lord Bird - Fanani, Abu Fanani; Nuri, Nuri Khilda Rahmatika; Rohim, Fathur Rohim; Syaikhu, Akhmad Syaikhu; Atiq, Atiq Mohammad Romdlon (Faculty of Letters, Universitas Dr. Soetomo, Surabaya, Indonesia, 2024)
The purpose of the study is to explore exploitation in James Mcbride’s the Good Lord Bird undergone mostly by the colored people because they are dominated by the white. Using descriptive and dramatic method to analyze as well as discuss the speech and action of the characters, the study finds that the colored people are exploited through two ways, man by man exploitation and labor exploitation. Man by man exploitation refers to enslaving, taking bribes, killing, and threatening, whilst, labor exploitation refers to selling by the owner and working for the owner. Thus, exploitation is an inhumane conduct since human should be respectable as they are created the same only those with great fear of the God.